Learning Difficulties in Listening Comprehension - Ryan Rayhana Sofyan; Andi Mushrihah (Makassar State University, 2019)
This paper aims at describing the student’s listening skill and their learning difficulties in listening comprehension. The method used was a descriptive method. The instruments were pre-TOEFL test and questionnaire. The population was the second year students of State University of Makassar. The results of this research are: the students have poor score in their listening comprehension and the students' learning difficulties in listening comprehension are: problem in interpretation, the lack of vocabulary, difficulty to concentrate, problem with lecturer's accent, confusion in similar phonemes, the speed of the speech problem in accent, problem in reduction and there are no repetitions and in learning media, the noise from students themselves, unclear sound, air conditioner problems and seat position. Based on the result, the writer concludes that the students' ability in listening comprehension is still poor, the teacher should motivate them to develop the habit of writing daily listening so that they can improve their skill.